Low tumor cell content predicts favorable prognosis in germinoma patients. Issue 1 (10th August 2021) - Takami, Hirokazu; Satomi, Kaishi; Fukuoka, Kohei; Fukushima, Shintaro; Matsushita, Yuko; Yamasaki, Kai; Nakamura, Taishi; Tanaka, Shota; Mukasa, Akitake; Saito, Nobuhito; Suzuki, Tomonari; Yanagisawa, Takaaki; et al.
Abstract: Background: Germinoma preferentially occurs in pediatric and young adult age groups. Although they are responsive to treatment with chemotherapy and radiation, the treatment may cause long-term sequelae in their later lives. Here, we searched for clinical and histopathological features to predict the prognosis of germinoma and affect treatment response. Methods: A total of 114 germinoma cases were included in the analysis. We investigated the association between clinical factors, tumor cell content, and progression-free survival (PFS). Results: The tumor cell content was widely distributed from <5% to 90% in the specimens, with a median value of 50%. Female patients showed higher tumor cell content in the specimens ( P = .002). Cases with lesions at atypical sites showed shorter PFS than those with lesions at other sites ( P = .03). Patients with a higher tumor cell content (≥50%) showed shorter PFS than those with a lower tumor cell content (<50%) ( P = .03). In multivariate analysis, tumor cell content was the only statistically significant prognostic factor ( P = .04). Among the 7 cases treated with local radiation and chemotherapy, all 3 cases that recurred (2 outside of the radiation field, 1 unknown) had tumor cell content of ≥50% in the original specimen, whereas all 4 cases without recurrence had tumor cell contents of <50%. Conclusions: We found that tumor cell content significantly affected the prognosis of germinomas. Although validation of these results using an independent and larger cohort is necessary, this potentially opens the possibility of leveraging this pathological factor in future clinical trials when stratifying the treatment intensity.